SPE Production and Operations Symposium 2013
DOI: 10.2118/164477-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pipe Diameter Effect on Liquid Loading in Vertical Gas Wells

Abstract: The effect of pipe diameter on liquid loading initiation has been experimentally investigated using 2-in and 4-in pipe diameters. Two-phase flow parameters such as pressure gradient and liquid holdup were measured. Flow characteristics were determined by visual observation using a high speed video camera. Critical gas flow rate for liquid loading initiation has been identified and comparison between the two pipe diameters is presented. The critical superficial gas velocity corresponding to the minimum pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In order to make such an evaluation, we have gathered an experimental databank (Table 2) of purely large pipe data of low-high gas flow from bubbly to annular flow. The databank consists of the current measurements in a 101.6 mm vertical pipe system (reported in previous sections); as well as the measurements of Zangana [28] and Van der Meulen [29] in 127 mm diameter flow loops at the University of Nottingham; and Skopich et al [30] in a 101.6 mm vertical pipe at the University of Tulsa, Oklahoma. The test facility, located in the PSE Laboratory at Cranfield University, comprises of three sections namely the fluid supply and metering section; test section; and the phase separation section.…”
Section: Void Fraction Correlations and Datamentioning
confidence: 99%
“…In order to make such an evaluation, we have gathered an experimental databank (Table 2) of purely large pipe data of low-high gas flow from bubbly to annular flow. The databank consists of the current measurements in a 101.6 mm vertical pipe system (reported in previous sections); as well as the measurements of Zangana [28] and Van der Meulen [29] in 127 mm diameter flow loops at the University of Nottingham; and Skopich et al [30] in a 101.6 mm vertical pipe at the University of Tulsa, Oklahoma. The test facility, located in the PSE Laboratory at Cranfield University, comprises of three sections namely the fluid supply and metering section; test section; and the phase separation section.…”
Section: Void Fraction Correlations and Datamentioning
confidence: 99%
“…The results suggested that one should not only consider Turner's or Wallis's criteria but also take into account the reservoir behavior when analyzing the liquid loading initiation. Different from Waltrich's research, Skopich et al (2015) did some researches on the influence of pipe diameter on the initiation of liquid loading. 2-in and 4-in ID pipes were used in the two-phase flow experiments.…”
Section: Introductionmentioning
confidence: 99%